Analisis Sistem Pengendalian Manajemen Dalam Sistem Insentif Karyawan Pada PT.Telekomunikasi Indonesia - Lisrotul Munawaroh; Bernike Trivena Noveliana; Hwihanus Hwihanus (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to analyze and find out how the management control system is implemented in the PT Telekomunikasi Indonesia incentive system and analyze and find out whether the management control system in the incentive system implemented can support effectiveness at PT Telekomunikasi Indonesia. The method used is the qualitative descriptive method, which is a research approach used to describe and explain a phenomenon or context without carrying out quantitative measurements or statistical analysis. This method focuses more on a deep understanding of the context, meaning and characteristics of a phenomenon. The existence of an incentive system at PT Telkom provides a number of benefits that can influence employee motivation, productivity and overall company performance in order to achieve company goals. Apart from that, the potential benefits obtained from PT Telkom's incentives are achieving company goals, work-life balance, increased creativity and innovation, and awards for achievements.